FUNCTIONAL ACTIVITY OF NEUTROPHILS IN CHRONIC RECURRENT FURUNCULOSIS - I. A. Novikovа (Medicinskaâ Immunologiâ, 2014)
Functional characteristics of neutrophils were evaluated in fifty-two patients with severe form ofchronic recurrent furunculosis, i.e., intensity of oxygen- and nitric oxide production, apoptosis rates, NET-forming properties, as well as phagocytic and bactericidal capacity. We have detected reduced efficiency ofintracellular pathogen killing, accompanied by a suppression of oxygen- and nitric oxide-producing reserve ofneutrophils. A compensatory increase in functional reserve of NET formation activity was also revealed, thusbeing a potential extracellular bactericidal mechanism for neutrophils. At the time of the disease exacerbation,we have found a decreased readiness for both spontaneous and stimulated neutrophil apoptosis.